ANALISIS FAKTOR FINANCIAL ATTITUDE, FINANCIAL BEHAVIOR, FINANCIAL KNOWLEDGE, PROPENSITY TO INDEBTEDNESS, COMPULSIVE BUYING DAN MATERIALISM TERHADAP FINANCIAL LITERACY DI MASYARAKAT KOTA BATAM - Dewi Khornida Marheni, (Rekaman : Riset Ekonomi Bidang Akuntansi dan Manajemen, 2020)
This study aimed to analyze the influence of financial attitude, financial behavior, and financial knowledge, the propensity to indebtedness, compulsive buying, and materialism on financial literacy. Primary data were obtained through distributing questionnaires totaling 410 sheets to the community in Batam and then processed using SPSS 21.0 software application. Conducted research revealed that there is significant positive effect of financial attitude, financial behavior towards financial literacy. While on the other hand, financial knowledge, the propensity to indebtedness does not have significant effect on financial literacy. Compulsive buying and materialism have  significant negative effect on financial literacy.